Execution quality and chargeback penalties in retail supply chains. Issue 1 (4th May 2020) - Craig, Nathan; DeHoratius, Nicole; Klabjan, Diego
Abstract: Retailers procure inventory by placing purchase orders (POs) with suppliers. POs specify product price, quantity, quality, delivery times, and other aspects of the fulfillment process, such as carton labeling requirements and packaging formats. When servicing an order, a supplier may fail to meet the fulfillment terms, thus committing a fulfillment error and triggering a chargeback penalty. We collect supplier compliance manuals from 111 retailers to characterize fulfillment errors and chargebacks in practice. The majority of chargeback penalties listed by retailers pertain to execution quality : aspects of the fulfillment process beyond product price, quantity, quality, and delivery time. We use an empirically grounded analytical model in combination with game‐theoretic analysis to demonstrate that the chargebacks most commonly used in practice do a poor job coordinating supply chains around execution quality.